ENVIRONMENTAL IMPACT OF ARTISANAL GOLD MINING AT CIKANGEAN RIVER IN MULYAJAYA VILLAGE, GARUT, WEST JAVA - Retno Damayanti; M. Lutfie Lutfie (Indonesian Mining Journal, 2009)
The artisanal and small scale gold mining usually utilize mercury for its gold recovery. Mercury is used as the best alternative by many miners due to its effectiveness, simple and cheap process for gold recovery. The increasing mercury utilization motivates tekMIRA to prevent more pollution caused by uncontrolled or incorrect mercury utilization. For this purpose, the artisanal gold mining located in Mulyajaya Village, Garut was chosen for monitoring mining activities. Grab sampling method was used to evaluate environmental monitoring on terrestrial water and its sediment, soil and tailing surrounding the artisanal gold mining. The monitoring results show that mercury was found in all waters and sediment surrounding the artisanal gold mine. The mercury concentration in river sediment was around 0.08 – 0.15 ppm and this was higher than its concentration in the river water (0.0002 ppm). The same concentration occurred at the upstream and downstream (0.0002 ppm). The mercury concentration in the sediment coming from sedimentation pond were 2.27 – 7.60 ppm. Eventhough the mercury was still in low concentration either in the water or in the sediment, a guidance should be delivered to the miners about the danger of mercury substances used in the mining activities.